Why is it worth reading Marx today? - Kozłowski, Marek (Hybris, 2014)
Using the first Polish edition of Marx’s Capital 1.1. Results of direct production process. Sixth chapter of the first Book of »Capital« (Project), PWN 2013, translated with an Epilogue by Mikołaj Ratajczak, as an anchoring point, the author investigates the conditions under which the answer to the title question can be affirmative. Namely, it is worth reading Marx today when our intellectual efforts not only tend towards enlarging our knowledge about his writings but also and most of all towards comprehending his philosophy.